Education and the Margins of Cyclical Adjustment in the Labor Market - Doniger, Cynthia L (Review of Economic Studies, 2026)
Abstract Allocative wages—the labor costs considered when deciding to form or dissolve a long-term employment relationship—are more sensitive to cyclical conditions for more educated workers. Specifically, college-educated workers’ allocative wages are highly pro-cyclical, while high school dropouts’ wages exhibit only moderate cyclicality. Further, as education increases, an increasing share of the sensitivity of allocative wages is driven by the persistent scarring effects of the cyclical position at the time of hiring on the wages associated with higher levels of tenure, amounting to more than a third of the overall sensitivity for the college educated. The greater job stability of the more educated—and therefore the exposure to scarring—contributes to these differences. In addition, more significant scarring at each horizon of tenure amplifies the effect. In service of documenting these facts, I develop new methods for inferring the sensitivity of labor costs to shocks when agents are forward-looking and wages may be intertemporally smoothed.